Thyroidectomy versus antithyroid drugs in Graves’ disease: a meta-analysis of randomized controlled trials - XiaoGang Zheng; Yi Zhu; Ming Gao Chen; Yong Cheng Su; Xiao Ming Wu (BMC Surgery)
Abstract Objective This meta-analysis was developed to compare the clinical outcomes associated with thyroidectomy and antithyroid drug treatment in Graves’ disease patients, with a focus on outcomes including ophthalmopathy onset or progress, the hyperthyroid cure rate, and the incidence of adverse events. Methods A systematic search of the PubMed, Web of Science, Embase, National Knowledge Infrastructure, China, and SinoMed databases was performed to identify randomized controlled trials (RCTs) comparing thyroidectomy and antithyroid drugs as treatments for Graves’ disease. Study quality was measured with the Cochrane risk of bias tool. Review Manager 5.4 and Stata 14.0 were employed to analyze the pooled data from these studies. The resultant data were reported as 95% confidence interval (CI) values and weighted mean differences. Fixed- or random-effects models were selected for pooled estimates based on the degree of heterogeneity among studies. Results Following a review of the literature, 7 RCTs enrolling 715 patients were incorporated into this meta-analysis. Thyroidectomy was associated with a significantly better hyperthyroid cure rate as compared to antithyroid drugs (OR 3.03, 95% CI: 1.05 to 8.97, P = 0.04), while also being associated with a lower rate of recurrence. Ophthalmopathy onset/worsening and adverse event incidence were comparable in both groups. Conclusion As compared to antithyroid drug administration, thyroidectomy can achieve higher hyperthyroid cure rates and a lower risk of recurrence in Graves’ disease patients without any concomitant rise in ophthalmopathy risk or adverse advent incidence. In cases where antithyroid drug treatment is not optimal, thyroidectomy can thus be recommended as a more promising approach to treating Graves’ disease.